Analisis Keuntungan Usaha Produksi Ayam Goreng Presto pada Produk Celebes Organik Chicken (COC) (Studi Kasus Program IbIKK di Fakultas Peternakan, Universitas Hasanuddin) - Muhammad Irfan Said; Effendi Abustam; Wempie Pakiding; . Hastang (Institut Pertanian Bogor, 2017)
This study aimed to analyze a number of profits from the sale of products fried chicken presto vaccum packed with brand Celebes Organic Chicken (COC). This product was developed from the activities of science and technology for innovation and campus creativity community service programs in the Faculty of Animal Science, Hasanuddin University. The process of production and sales made at the Laboratory of Meat and Egg Processing Technology, Faculty of Animal Science, Hasanuddin University. The production process done through several processes, namely: washing, seasoning, cooking, refrigeration, vacuum packing, and freezing. Based on the results of the data analysis of the benefit and costs of product sales result that, on the scale of business of 5 chickens with 1.5–1.6 kg carcass weight (10 pieces of chicken) (17 packsto produce the amount of fixed costs by IDR 4.778.333, variable costs IDR 5.660.000, the benefit of IDR 13.175.000, and the benefit of IDR 2.736.667. The end result of this calculation concluded that this business is very profitable, so it is feasible to be developed into a business. The profit margin obtained IDR 4.123/pack.